Analisis Penerapan AKAD Rahn Tasjily Pada Pegadaian Syariah Bukittinggi (Studi: Pegadaian UPS Manggis Ganting, Bukittinggi) - Nursyafni Syafia; Bambang Kurniawan; Khusnul Istiqomah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research was motivated by the small number of customers at the Rahn Tasjily Agreement at Pegadaian UPS Manggis Bukittinggi. The purpose of this research is to find out how the Rahn Tasjily Agreement is implemented at the UPS Manggis Bukittinggi pawnshop and also to find out the obstacles faced in implementing the Rahn Tasjily Agreement. This research includes field study research with qualitative descriptive methods, and uses primary and secondary data sources, as well as data collection techniques through interviews, observation and documentation. The research results obtained by the author after analyzing the data are the marketing strategy implemented by the UPS Manggis Bukittinggi pawnshop in implementing the Rahn Tasjily Agreement, namely by using Crossselling, Upselling, Literacy. The pricing strategy is good. The implementation of the contract is also good, where the product is made to help people who want to borrow money for business capital, but in terms of promotion it is not optimal. The obstacles faced by the UPS Manggis Bukittinggi pawnshop in implementing the Rahn Tasjily Agreement are limited marketing time, inadequate promotional facilities and a lack of public understanding of the Rahn Tasjily Agreement.